“Evaluación de seis soluciones nutritivas compuestas por humus de lombriz (eisenia foetida) y fertilizantes químicos en el cultivo hidropónico del tomate (lycopersicon sculentum)” - Guerrero Santa Cruz, Beslinder (2009)
This research work was realized in Tarapoto city department san martín it is located Nº 366 Manco Inca 366 street village 9 April, the work had a time approximately 4 moths ~go it beginning in October, 2007. The work consisted in the production of tomate evaluating the variety "RIO GRANDE" using 5 nutritive solutions it was compound by humus of earth worm lixiviate and chemicals fertilizers it had sand as a substratum more husk ok rice compared with a evidence it had a substratum salid humus then in all the treatment 1 used a quantity 1,5 Kg. humus for each plant 1 used the dosing completely the to random with 6 treatments and 3 repletion's respectively. The targets of this work were to evaluate the performance of crop tomate fertilized with 6 nutritive solutions compound by humus earth worm (Eisenia foetida) and chemicals fertilizers in the development grow crop tomate under the system hydroponic, this way in determined the nutritive solution that allowed the best grow up plant and the majar cost production and it's relation cost/benefit different treatments. For realize the present work 1 built a greenhouse with materials a total area of 28M2 this result T 3(solution 4) the majar performance with 310,09 TMIHa, it had a benefit net SI 81,441.15 in wich cost/benefit it was 73,34%. Ther the treatments the evidence To (hums salid substrate solution 1) it resulted be uneconomical with a less SI 139,177.10 in which cost/beneficit was 267, 74%.